Implementasi Konsep Perikanan Tangkap dalam Pemberdayaan Masyarakat Pesisir Oesapa di Kota Kupang - Patrikcs Lazarus Dedo Ngara; Fransina W. Ballo; Novi Theresia Kiak (MENAWAN : Jurnal Riset dan Publikasi Ilmu Ekonomi, 2024)
The aim of this research is to determine the government's efforts to economically empower the fishing community in the Oesapa fishing village, Kupang City and determine the impact of the assistance provided by the government on community welfare. This research uses a qualitative descriptive approach. Data collection used was interviews, observation and documentation. The results of the research show that the government's efforts to empower the fishing community's economy are by optimizing fishing facilities and infrastructure that are not yet fully distributed among fishermen, improving the quality of fishermen's human resources through socialization to help the community increase community awareness of ocean sustainability, and finally utilizing marine resources and fisheries which have a positive impact on the welfare of both fishermen.